Development of photovoltaic powered greenhouse for the application in Peninsular Malaysia - Choong P.Y.; Chua Y.L.; Ker P.J.; Ramasenderan N. (American Institute of Physics, 2025)
Photosynthetically Active Radiation (PAR) is crucial towards crop growth and development, better understanding is needed to determine the relationship between roof mounted PV panels on a PV powered greenhouse and amount of PAR entering the PV powered greenhouse. This study seeks to determine the optimal arrangement of PV module installed on roof of PV greenhouse in terms of Photosynthetically Active Radiation (PAR) available for crops cultivated within PV greenhouse. Three different prototypes were developed for this research, namely control unit without any PV panels installed on roof, straight-line PV array greenhouse and checkerboard PV array greenhouse and data collection was performed for five (5) continuous days. Based on the obtained results, it was found that from the PV greenhouse with straight line PV array allows for highest PAR value within greenhouse, whilst also allowing for PV energy production with minimal compromising on PAR available for crop cultivation. ? 2024 Author(s).